Analisis Kelayakan Pengembangan Ekowisata Mangrove di Pantai Muara Indah Kecamatan Pantai Labu Kabupaten Deli Serdang - Fathul Khoiri; Budi Utomo; Indra Lesmana (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2014)
Mangrove forests in Pantai Muara Indah was a buffer and tourism area were located in Denai Kuala Village. Purpose of this research was to asses the potential of mangrove forests, such as type, closure, and fauna of the mangrove forest with visual method. Setting a strategy for sustainable tourism development in the mangrove in Pantai Muara Indah with SWOT analysis .This research found 8 species of mangroves, Avicennia lanata, Avicennia marina, Bruguieira exaristata, Bruguieira gymnorrhyza, Excoecaria agallocha, Hibiscus tiliaceus Rhizophora apiculata, Rhizophora mucronata. Fauna were found in this research area consisted of fish, crustaceans, primates and birds. People around the mangrove forests agree with the ecotourism development activities. The results of the feasibility development analysis with 3 aspects: ecology with the score 36,8, socioeconomic score 22,6, and supporting criteria with a score 9,6, according to criteria of feasibility assessment of tourism development mangrove forests in Muara Indah Beach was feasible to be developed 69,5.Keywords : Ecotourism, Mangrove Ecosystems, Pantai Muara Indah.